Research trends in emotion regulation of high school students in Indonesia - Nur Wisma; Alrefi Alrefi; Fadhlina Rozaqqyah; Nurmala Dewi; Nadya Permata Sari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Emotion regulation is an individual's ability to recognise, manage and express emotions adaptively in various life situations. In adolescents, especially high school students in Indonesia, this ability is crucial considering that adolescence is a developmental phase full of emotional and social challenges. This study aims to explore the dynamics of emotion regulation in high school students in Indonesia and identify factors that influence this ability. The research was conducted using a qualitative approach with a literature study method that reviewed twenty relevant national and international scientific journals. The selection of journals was based on the suitability of the topic, the quality of the methodology, and its contribution to the understanding of emotion regulation in the context of adolescent education. The results showed that emotion regulation in high school students is influenced by intrapersonal factors, family environment, peer relations, and academic pressure. This study specifically highlights emotion regulation strategies such as cognitive reappraisal, impulse control, and achieving emotional balance in the school environment. The novelty of this research lies in the contextual focus on Indonesian students and the emphasis on the importance of preventive and educative approaches in building emotion regulation skills as part of mental readiness for the future.